EFFECT OF APIS-MELLIFERA BEE VENOM AND GAMMA-RADIATION ON BONE-MARROW CELLS OF WISTAR RATS TREATED INVIVO - Varanda, Eliana Aparecida [UNESP]; Takahashi, C. S.; Soares, AEE; Barreto, SAJ (Soc Brasil Genetica, 1992)
To determine whether the venom of Apis mellifera can exert a radioprotective effect, by reducing the frequency of chromosome aberrations induced by radiation, five different experiments were performed on bone marrow cells of Wistar rats.Animals weighing about 100 g were injected intraperitoneally with different venom concentrations (1.0 or 0.5 mul) 1 or 24 h before, or 30 min after being submitted to 3 or 4 Gy of gamma radiation, and sacrificed 24 h after the last treatment. For each experiment in addition to the group of animals submitted to combined treatment (venom + radiation) and to their control, there was also one group treated with radiation only and another treated with venom only. A decrease in the frequency of chromosome aberrations, and fragments in particular, as well as in the number of cells with aberrations was observed in the experiments in which venom was administered 24 h before irradiation, and the effect was more marked at the higher venom concentration (1 mul/100 g weight).